Visual Attention to Reference Frames Affects Perceptions of Shape from Shading. Issue 3 (June 2014) - Sasaki, Hiroyuki
Perception of shape from shading is processed locally in a bottom-up manner, but is also influenced by global or contextual factors. This study examined the influence of attention to the reference frame on the perception of shape from shading. In a visual search task, participants were asked to identify the location of a target relative to the reference frame. The results showed that shaded targets were more quickly and accurately detected when the shading gradient was parallel, rather than orthogonal, to the orientation of the environmental reference frame. This was further supported by a second experiment with a masking paradigm. Consequently, the perceptual process of shape from shading may be a flexible mechanism in which the representation of gradient orientation is calibrated by top-down processing in visual attention.